PENGARUH IMPLEMENTASI KURIKULUM MERDEKA TERHADAP PENGEMBANGAN CRITICAL THINKING SISWA DALAM PEMBELAJARAN PAI DI SMP MUHAMMADIYAH 7 MEDAN - Iqbal Maladzie; Muhammad Azhari; Eka Zul Wahyudi (PT. Hasba Edukasi Mandiri, 2025)
This study was conducted at SMP Muhammadiyah 7 Medan with the aim of analyzing the relationship between the implementation of the Kurikulum Merdeka (Independent Curriculum) and students’ critical thinking skills in Islamic Education (PAI) learning. The research employed a correlational design with a quantitative approach to determine the strength or weakness of the relationship between the two variables. The study population consisted of all students at SMP Muhammadiyah 7 Medan, and a sample of 25 respondents was selected using random sampling. Data were collected through questionnaires, observations, and documentation. Primary data were obtained from students’ questionnaire responses, while secondary data were sourced from school documents, observation results, and relevant literature on the Kurikulum Merdeka and critical thinking skills in PAI learning. The research findings reveal that: (1) the score for variable X reached 2210 out of a maximum of 2500, with an achievement percentage of 88.4%, categorized as High. This indicates that the implementation of the Kurikulum Merdeka in PAI learning has been carried out effectively. (2) Students’ critical thinking skills scored 2228 out of 2500, or 89%, also categorized as High. (3) Regression analysis produced the equation ???? = 31.832 + 0.648????. The regression coefficient of 0.648 signifies that each one-point increase in the implementation score of the Kurikulum Merdeka contributes to a 0.648-point increase in students’ critical thinking skills. The t-test result shows t-count = 3.710 > t-table = 1.678 with sig = 0.001 < 0.05, indicating a significant relationship between variables X and Y. Thus, the better the implementation of the Kurikulum Merdeka, the higher the students’ critical thinking skills.